Gothenburg hills: Design methodologies employing local context - Hansson, Joar (My University, 2022)
The purpose of this thesis was to explore architectural design through the development of a design method. The method was established with the objective of exploring ways to identify and interpret aspects of local context and regional characteristics, as well as how to inform a design process by addressing such aspects. The project was carried out by engaging with a site which itself possesses characteristics typical for the greater region. Specifically, the entry point to the topic of regional characteristics was the variance in topography, which in Gothenburg with its many peaks and valleys certainly is evident. With a base in site conditions, immediate aspects such as natural materials and textures were explored, but also other more external factors, which originate from the views offered by the site. Said site is a piece of unbuilt public land on top of a hill, bordering a quiet back street whilst within close proximity to an urban node. For the reason of keeping the land public, together with a need for new premises expressed by the local district library, the choice was made to use a public library as building program within the project. The thesis relates to discourses within regionalism and contextualism as input for architectural design, and was informed by written as well as built work that in different ways deal with these themes. Sampling and reinterpreting were together important design strategies for the process and were used as a way to communicate clarity about adopting contextual references, while avoiding too literal gestures. The result of the thesis is a building whose design originates from a range of different ways to reference local context. In other words, the outcome can be described as a mixture of strategies, which have the incentive to involve certain local characteristics in the design in common.